Preparation method of cubic phase gadolinium oxide transparent ceramic for scintillator matrix
By mixing nano- and micro-sized gadolinium oxide powders in a specific ratio and sintering them at low temperature for a long time, the densification problem of cubic phase gadolinium oxide ceramics was solved, resulting in transparent gadolinium oxide ceramics with high density and high transparency, meeting the requirements of high-efficiency scintillators.
Patent Information
- Application Number
- CN202411629170.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-07
AI Technical Summary
Existing technologies make it difficult to prepare high-density cubic gadolinium oxide transparent ceramics, resulting in low optical transmittance, which cannot meet the requirements of high-efficiency scintillators.
Cubic phase gadolinium oxide nanoparticles with a particle size of less than or equal to 50 nm and monoclinic phase micron gadolinium oxide powders with a particle size between 800 nm and 2 μm are mixed in a specific ratio, and the monoclinic phase lattice expands and transforms into the cubic phase through a low-temperature long-time sintering method, thereby achieving ceramic densification.
High-density cubic gadolinium oxide transparent ceramics were prepared, with an optical transmittance of 22.6% in the visible light range. This is the first time that cubic gadolinium oxide ceramics have achieved complete transparency, with a density of 99.6%.
Smart Images

Figure CN119263829A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optical functional materials, and in particular relates to a method for preparing cubic phase gadolinium oxide transparent ceramics for scintillator matrix. Background Art
[0002] Rare earth scintillating ceramics are a type of optical functional material that can convert high-energy radiation (high-speed particles, X-rays, gamma rays) into directly detectable ultraviolet or visible light. They are widely used in many fields such as radiation medicine, high-energy physics, nuclear physics, industrial testing, geological exploration, and safety inspection. At present, most of the research on rare earth scintillating ceramics is focused on yttrium-based or lutetium-based materials such as yttrium aluminum garnet, yttrium oxide, lutetium aluminum garnet, and lutetium oxide. As the service environment becomes increasingly harsh, higher requirements are placed on the scintillation efficiency of scintillating ceramics. High-efficiency scintillators require the material itself to have a high theoretical density and a large effective atomic number. Yttrium aluminum garnet (4.55 g / cm 3 ) and yttrium oxide (5.03 g / cm 3 ) has a low density, so its ability to block radiation is weak. In order to increase the density of both, researchers at home and abroad have added higher density cubic phase gadolinium oxide (7.606 g / cm 3 ), to produce (Y,Gd)AG:Ce with stronger radiation blocking ability 3+ and(Y,Gd) 2 O 3 :Eu 3+ , but its density is still far behind that of single-phase cubic gadolinium oxide. 3 ) and lutetium oxide (9.4 g / cm 3 ), although lutetium has a large atomic number and high density, the market price of lutetium oxide is expensive, resulting in high preparation costs. The price of gadolinium oxide is similar to that of yttrium oxide, much lower than that of lutetium oxide, and the atomic number of gadolinium is 64, the atomic weight is 157, which is closest to the lanthanide element lutetium (175) with the largest atomic weight, so cubic phase gadolinium oxide ceramics are a potential rare earth scintillating matrix material.
[0003] However, there are two difficulties in the preparation of cubic gadolinium oxide ceramics. First, when the sintering temperature is higher than 1250°C, the optically isotropic cubic phase will transform into an optically anisotropic monoclinic phase, resulting in the inability of light to penetrate the ceramic block. In addition, the phase transition from the cubic phase to the monoclinic phase causes the volume of the block material to shrink, making it difficult to sinter the ceramic to a dense state, which also results in the ceramic block having no optical transmittance. Second, when the sintering temperature is lower than 1250°C, the ceramic will also be difficult to sinter to a dense state, affecting its optical transmittance. Therefore, how to obtain high-density cubic gadolinium oxide transparent ceramics to meet the needs of future detectors for high-efficiency scintillators is an urgent problem that technicians in this field need to solve. Summary of the invention
[0004] The present invention aims at the problems existing in the prior art and provides a method for preparing a cubic phase gadolinium oxide transparent scintillating ceramic used as a scintillator matrix.
[0005] It should be noted that in order to simultaneously meet the requirements of the cubic phase and high density of gadolinium oxide ceramics, the present invention promotes the expansion of the monoclinic phase lattice and transforms it back to the cubic phase by mixing cubic phase gadolinium oxide nanopowder and monoclinic phase gadolinium oxide micron powder according to a certain mass fraction ratio, forming, and sintering at low temperature for a long time, so that the monoclinic phase lattice expands and transforms back to the cubic phase. While the lattice expands, the densification of the gadolinium oxide ceramics is promoted. Based on this, the cubic phase gadolinium oxide transparent ceramics for scintillator matrix developed by the present invention follow the following principles in the preparation process: (1) The gadolinium oxide nanopowder is a cubic phase with a particle size of less than or equal to 50 nm; (2) Gadolinium oxide micron powder is monoclinic phase with particle size ranging from 800 nm to 2 μm; (3) The cubic nanopowder and the monoclinic micron powder are mixed in a mass fraction ratio of 9:1 to 6.5:3.5; (4) The ceramic sintering temperature is lower than the phase transition point temperature of 1250℃ (the temperature at which the cubic phase transforms to the monoclinic phase).
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A cubic gadolinium oxide transparent ceramic for a scintillator matrix. The ceramic is prepared by mixing cubic nano-gadolinium oxide powder with a particle size of less than or equal to 50 nm and micron-gadolinium oxide powder with a particle size between 800 nm and 2 μm as raw materials according to a mass fraction ratio of 9:1 to 6.5:3.5.
[0007] According to the present invention, the preparation method of the cubic phase gadolinium oxide transparent ceramic for scintillator matrix comprises the following specific steps: S1: Mix cubic nano-gadolinium oxide powder with a particle size of less than or equal to 50 nm and monoclinic micro-gadolinium oxide powder with a particle size between 800 nm and 2 μm in a mass ratio of 9:1 to 6.5:3.5, then ball-mill for 24 h, put the ball-milled slurry into an oven for drying, and sieve to obtain a mixed powder; S2: dry-pressing the mixed powder obtained in step S1 under 50-150 MPa by axial unidirectional pressure for 2-3 min to obtain a formed body; S3: Dry the formed body obtained in step S2, and then perform cold isostatic pressing treatment at a pressure range of 200-300 MPa and a holding time of 3-6 min. Finally, perform long-term sintering at low temperature and normal pressure at a sintering temperature of 1000-1200 °C and a holding time of 100-300 hours to finally obtain a cubic phase gadolinium oxide transparent ceramic for a scintillator matrix.
[0008] The method for preparing cubic phase gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm comprises the following specific steps: SS1: Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 0.5 mol / L citric acid solution, according to the molar ratio of metal cation to citric acid of 1:0.8~1.5, mix the two solutions and stir at room temperature for 10 minutes, then add 2 ml ethylene glycol to the mixed solution, heat and stir at 90 °C until the mixed solution becomes a colorless transparent sol; SS2: The colorless and transparent sol in step S1 is transferred to a forced air drying oven for drying at 200°C for 2 hours to obtain a fluffy yellow precursor; SS3: The yellow precursor obtained in step S2 is placed in a muffle furnace and calcined at 400-800° C. for 4 hours to obtain cubic gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm.
[0009] The method for preparing the monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm comprises the following specific steps: SSS1: Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 1 mol / L urea solution, mix the two solutions according to the stoichiometric ratio, heat and stir in a 96 ℃ water bath for 2 hours until a white precipitate is formed; SSS2: The white precipitate solution described in SS1 was centrifuged, and the obtained white precipitate product was repeatedly washed with deionized water and anhydrous ethanol, and then dried in a drying oven at 80°C for 24 hours to obtain a white precursor powder; SSS3: The white precursor powder described in SS2 is placed in a high-temperature muffle furnace and calcined at 1300-1600 °C for 2 hours to obtain monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm.
[0010] The beneficial effects of the present invention are The gadolinium oxide transparent ceramics in the present invention have achieved a completely cubic phase for the first time, and are transparent in the visible light range. The monoclinic phase is completely transformed into a cubic phase through long-term low-temperature sintering. The lattice expansion during the transformation process promotes the densification of the gadolinium oxide ceramics, and its density is as high as 99.6%. The successful preparation of cubic phase gadolinium oxide transparent ceramics solves the technical problem of low scintillation efficiency of existing scintillator matrix materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a transmission image of the cubic gadolinium oxide nanopowder obtained in Example 1 of the present invention; Figure 2 This is a scanned image of the monoclinic micron powder obtained in Example 1 of the present invention; Figure 3 The XRD spectrum of the cubic gadolinium oxide transparent ceramic obtained in Example 1 of the present invention; Figure 4 This is a scanned image of the cubic gadolinium oxide transparent ceramic obtained in Example 1 of the present invention; Figure 5 This is the transmittance spectrum of the cubic gadolinium oxide transparent ceramic obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0012] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0013] The invention provides a method for preparing a cubic gadolinium oxide transparent ceramic for a scintillator matrix. The method comprises mixing cubic gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm and monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm as raw materials. When the cubic gadolinium oxide nanopowder and the monoclinic gadolinium oxide micron powder are mixed, the mass ratio of the two powders is 9:1 to 6.5:3.5. The mixture is then ball-milled, sieved, formed and sintered to obtain a completely cubic gadolinium oxide transparent ceramic.
[0014] The following is a description of the features and effects of the present invention in conjunction with specific embodiments: Example 1
[0015] (1) Prepare 0.5 mol / L Gd(NO 3 ) 3Gadolinium nitrate solution, prepare 0.5 mol / L citric acid solution, according to the molar ratio of metal cation to citric acid of 1:0.8, mix the two solutions and stir at room temperature for 10 minutes, then add 2 ml ethylene glycol to the mixed solution, heat and stir at 90 °C until the mixed solution becomes a colorless transparent sol; (2) The colorless transparent sol was transferred to a forced air drying oven for drying at 200 °C for 2 hours to obtain a fluffy yellow precursor; (3) placing the obtained yellow precursor in a muffle furnace and calcining it at 600° C. for 4 hours to obtain cubic gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm; (4) Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 1 mol / L urea solution, mix the two solutions according to the stoichiometric ratio, heat and stir in a 96 ℃ water bath for 2 hours until a white precipitate is formed; (5) The white precipitate solution was centrifuged, and the obtained white precipitate product was repeatedly washed with deionized water and anhydrous ethanol, and then dried in a drying oven at 80 °C for 24 hours to obtain a white precursor powder; (6) placing the white precursor powder into a high-temperature muffle furnace and calcining it at 1300 °C for 2 hours to obtain monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm; (7) mixing cubic nano-gadolinium oxide nanopowder and monoclinic micro-gadolinium oxide powder in a mass ratio of 9:1, and then ball milling for 24 hours. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed powder; (8) The obtained mixed powder is dry pressed by axial uniaxial pressure at 120 MPa for 2 min to obtain a molded body; (9) The obtained molded body was dried and then cold isostatically pressed at a pressure of 200 MPa for a holding time of 3 min. It was then sintered at low temperature and long time at normal pressure at a sintering temperature of 1000 °C for a holding time of 100 h to finally obtain a cubic phase gadolinium oxide transparent ceramic for a scintillator matrix.
[0016] Figure 1 This is a transmission photograph of cubic phase gadolinium oxide nanopowder. It can be seen from the figure that the average particle size of the sample is about 20 nm; Figure 2 This is a scanned image of monoclinic gadolinium oxide micron powder. It can be seen from the figure that the average particle size of the sample is about 1 μm; Figure 3This is the XRD spectrum of cubic gadolinium oxide transparent ceramics. It can be seen from the figure that after being kept at 1000 ℃ for 100 hours, the phase of the sample has completely transformed into a cubic phase. Figure 4 This is a scanned image of cubic gadolinium oxide transparent ceramics. It can be seen from the image that there are a small number of pores in the sample. The density of the sample was measured by the Archimedean drainage method, and its density was as high as 99.6%, achieving the high density of cubic gadolinium oxide ceramics for the first time. Figure 5 This is the transmittance spectrum of cubic gadolinium oxide transparent ceramics. It can be seen from the figure that in the visible light range of 400-800 nm, the maximum transmittance of the sample reached 22.6%, realizing the transparency of cubic gadolinium oxide bulk in the visible light range for the first time. Example 2
[0017] (1) Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 0.5 mol / L citric acid solution, according to the molar ratio of metal cation to citric acid of 1:0.8, mix the two solutions and stir at room temperature for 10 minutes, then add 2 ml ethylene glycol to the mixed solution, heat and stir at 90 °C until the mixed solution becomes a colorless transparent sol; (2) The colorless transparent sol was transferred to a forced air drying oven for drying at 200 °C for 2 hours to obtain a fluffy yellow precursor; (3) placing the obtained yellow precursor in a muffle furnace and calcining it at 400° C. for 4 hours to obtain cubic gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm; (4) Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 1 mol / L urea solution, mix the two solutions according to the stoichiometric ratio, heat and stir in a 96 ℃ water bath for 2 hours until a white precipitate is formed; (5) The white precipitate solution was centrifuged, and the obtained white precipitate product was repeatedly washed with deionized water and anhydrous ethanol, and then dried in a drying oven at 80 °C for 24 hours to obtain a white precursor powder; (6) placing the white precursor powder into a high-temperature muffle furnace and calcining it at 1300 °C for 2 hours to obtain monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm; (7) mixing cubic nano-gadolinium oxide nanopowder and monoclinic micro-gadolinium oxide powder in a mass ratio of 8:2, and then ball milling for 24 hours. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed powder; (8) The obtained mixed powder is dry pressed by axial uniaxial pressure at 120 MPa for 2 min to obtain a molded body; (9) The obtained molded body was dried and then cold isostatically pressed at a pressure of 200 MPa for a holding time of 3 min. It was then sintered at low temperature and long time at normal pressure at a sintering temperature of 1000 °C for a holding time of 100 h to finally obtain a cubic phase gadolinium oxide transparent ceramic for a scintillator matrix. Example 3
[0018] (1) Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 0.5 mol / L citric acid solution, according to the molar ratio of metal cation to citric acid of 1:0.8, mix the two solutions and stir at room temperature for 10 minutes, then add 2 ml ethylene glycol to the mixed solution, heat and stir at 90 °C until the mixed solution becomes a colorless transparent sol; (2) The colorless transparent sol was transferred to a forced air drying oven for drying at 200 °C for 2 hours to obtain a fluffy yellow precursor; (3) placing the obtained yellow precursor in a muffle furnace and calcining it at 400° C. for 4 hours to obtain cubic gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm; (4) Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 1 mol / L urea solution, mix the two solutions according to the stoichiometric ratio, heat and stir in a 96 ℃ water bath for 2 hours until a white precipitate is formed; (5) The white precipitate solution was centrifuged, and the obtained white precipitate product was repeatedly washed with deionized water and anhydrous ethanol, and then dried in a drying oven at 80 °C for 24 hours to obtain a white precursor powder; (6) placing the white precursor powder into a high-temperature muffle furnace and calcining it at 1300 °C for 2 hours to obtain monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm; (7) mixing cubic nano-gadolinium oxide nanopowder and monoclinic micro-gadolinium oxide powder in a mass ratio of 8:2, and then ball milling for 24 hours. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed powder; (8) The obtained mixed powder is dry pressed by axial uniaxial pressure at 120 MPa for 2 min to obtain a molded body; (9) The obtained molded body was dried and then cold isostatically pressed at a pressure of 200 MPa for a holding time of 3 min. It was then sintered at low temperature and long time at normal pressure at a sintering temperature of 1000 °C for a holding time of 100 h to finally obtain a cubic phase gadolinium oxide transparent ceramic for a scintillator matrix. Example 4
[0019] (1) Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 0.5 mol / L citric acid solution, according to the molar ratio of metal cation to citric acid of 1:0.8, mix the two solutions and stir at room temperature for 10 minutes, then add 2 ml ethylene glycol to the mixed solution, heat and stir at 90 °C until the mixed solution becomes a colorless transparent sol; (2) The colorless transparent sol was transferred to a forced air drying oven for drying at 200 °C for 2 hours to obtain a fluffy yellow precursor; (3) placing the obtained yellow precursor in a muffle furnace and calcining it at 600° C. for 4 hours to obtain cubic gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm; (4) Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 1 mol / L urea solution, mix the two solutions according to the stoichiometric ratio, heat and stir in a 96 ℃ water bath for 2 hours until a white precipitate is formed; (5) The white precipitate solution was centrifuged, and the obtained white precipitate product was repeatedly washed with deionized water and anhydrous ethanol, and then dried in a drying oven at 80 °C for 24 hours to obtain a white precursor powder; (6) placing the white precursor powder into a high-temperature muffle furnace and calcining it at 1500 °C for 2 hours to obtain monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm; (7) mixing cubic nano-gadolinium oxide nanopowder and monoclinic micro-gadolinium oxide powder in a mass ratio of 7:3, and then ball milling for 24 hours. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed powder; (8) The obtained mixed powder is dry pressed by axial uniaxial pressure at 120 MPa for 2 min to obtain a molded body; (9) The obtained molded body was dried and then cold isostatically pressed at a pressure of 200 MPa for a holding time of 3 min. It was then sintered at low temperature and long time at normal pressure at a sintering temperature of 1000 °C for a holding time of 100 h to finally obtain a cubic phase gadolinium oxide transparent ceramic for a scintillator matrix. Example 5
[0020] (1) Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 0.5 mol / L citric acid solution, according to the molar ratio of metal cation to citric acid of 1:0.8, mix the two solutions and stir at room temperature for 10 minutes, then add 2 ml ethylene glycol to the mixed solution, heat and stir at 90 °C until the mixed solution becomes a colorless transparent sol; (2) The colorless transparent sol was transferred to a forced air drying oven for drying at 200 °C for 2 hours to obtain a fluffy yellow precursor; (3) placing the obtained yellow precursor in a muffle furnace and calcining it at 800° C. for 4 hours to obtain cubic gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm; (4) Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 1 mol / L urea solution, mix the two solutions according to the stoichiometric ratio, heat and stir in a 96 ℃ water bath for 2 hours until a white precipitate is formed; (5) The white precipitate solution was centrifuged, and the obtained white precipitate product was repeatedly washed with deionized water and anhydrous ethanol, and then dried in a drying oven at 80 °C for 24 hours to obtain a white precursor powder; (6) placing the white precursor powder into a high-temperature muffle furnace and calcining it at 1500 °C for 2 hours to obtain monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm; (7) Mixing cubic nano-gadolinium oxide nanopowder and monoclinic micro-gadolinium oxide powder in a mass ratio of 6.5:3.5, then ball milling for 24 hours, drying the ball-milled slurry in an oven, and sieving to obtain a mixed powder; (8) The obtained mixed powder is dry pressed by axial uniaxial pressure at 120 MPa for 2 min to obtain a molded body; (9) The obtained molded body was dried and then cold isostatically pressed at a pressure of 200 MPa for a holding time of 3 min. It was then sintered at low temperature and long time at normal pressure at a sintering temperature of 1100 °C for a holding time of 200 h to finally obtain a cubic phase gadolinium oxide transparent ceramic for a scintillator matrix. Example 6
[0021] (1) Prepare 0.5 mol / L Gd(NO 3 ) 3Gadolinium nitrate solution, prepare 0.5 mol / L citric acid solution, according to the molar ratio of metal cation to citric acid of 1:0.8, mix the two solutions and stir at room temperature for 10 minutes, then add 2 ml ethylene glycol to the mixed solution, heat and stir at 90 °C until the mixed solution becomes a colorless transparent sol; (2) The colorless transparent sol was transferred to a forced air drying oven for drying at 200 °C for 2 hours to obtain a fluffy yellow precursor; (3) placing the obtained yellow precursor in a muffle furnace and calcining it at 700° C. for 4 hours to obtain cubic gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm; (4) Prepare 0.5 mol / L Gd(NO 3 ) 3 Gadolinium nitrate solution, prepare 1 mol / L urea solution, mix the two solutions according to the stoichiometric ratio, heat and stir in a 96 ℃ water bath for 2 hours until a white precipitate is formed; (5) The white precipitate solution was centrifuged, and the obtained white precipitate product was repeatedly washed with deionized water and anhydrous ethanol, and then dried in a drying oven at 80 °C for 24 hours to obtain a white precursor powder; (6) placing the white precursor powder into a high-temperature muffle furnace and calcining it at 1300 °C for 2 hours to obtain monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm; (7) mixing cubic nano-gadolinium oxide nanopowder and monoclinic micro-gadolinium oxide powder in a mass ratio of 9:12, then ball milling for 24 h, placing the ball-milled slurry in an oven for drying, and sieving to obtain a mixed powder; (8) The obtained mixed powder is dry pressed by axial uniaxial pressure at 120 MPa for 2 min to obtain a molded body; (9) The obtained molded body was dried and then cold isostatically pressed at a pressure of 200 MPa for a holding time of 3 min. It was then sintered at low temperature and long time at normal pressure at a sintering temperature of 1200 °C for a holding time of 100 h to finally obtain a cubic phase gadolinium oxide transparent ceramic for a scintillator matrix.
Claims
1. A method for preparing a cubic phase gadolinium oxide transparent ceramic for a scintillator matrix, characterized in that: The cubic gadolinium oxide ceramic is prepared by mixing cubic gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm and monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm as raw materials. When the cubic gadolinium oxide nanopowder and the monoclinic gadolinium oxide micron powder are mixed, the mass ratio of the two is 9:1 to 6.5:3.
5. The preparation method of the ceramic comprises the following steps: S1: Mix cubic nano-gadolinium oxide nanopowder and monoclinic micro-gadolinium oxide powder in a mass ratio of 9:1-6.5:3.5, then ball-mill for 24 h, put the ball-milled slurry into an oven for drying, and sieve to obtain a mixed powder; S2: dry-pressing the mixed powder obtained in step S1 under 50-150 MPa by axial unidirectional pressure for 2-3 min to obtain a formed body; S3: drying the formed green body obtained in step S2, and then performing a cold isostatic pressing process, and then sintering by increasing the temperature, so as to finally obtain a cubic phase gadolinium oxide transparent ceramic for a scintillator matrix; The method for preparing cubic phase gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm comprises the following specific steps: SS1: Prepare 0.5 mol / L Gd(NO3)3 gadolinium nitrate solution and 0.5 mol / L citric acid solution, and stir the two solutions at room temperature for 10 minutes according to the molar ratio of metal cation to citric acid of 1:0.8-1.
5. Then add 2 ml ethylene glycol to the mixed solution, heat and stir at 90 °C until the mixed solution becomes a colorless transparent sol; SS2: The colorless and transparent sol in step S1 is transferred to a forced air drying oven for drying at 200°C for 2 hours to obtain a fluffy yellow precursor; SS3: placing the yellow precursor obtained in step S2 into a muffle furnace and calcining it at 400-800° C. for 4 hours to obtain cubic gadolinium oxide nanopowder with a particle size of less than or equal to 50 nm; The method for preparing the monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm comprises the following specific steps: SSS1: Prepare 0.5 mol / L Gd(NO3)3 gadolinium nitrate solution and 1 mol / L urea solution, mix the two solutions according to the stoichiometric ratio, heat and stir in a 96 °C water bath for 2 hours until a white precipitate is formed; SSS2: The white precipitate solution described in SS1 was centrifuged, and the obtained white precipitate product was repeatedly washed with deionized water and anhydrous ethanol, and then dried in a drying oven at 80°C for 24 hours to obtain a white precursor powder; SSS3: The white precursor powder described in SS2 is placed in a high-temperature muffle furnace and calcined at 1300-1600 °C for 2 hours to obtain monoclinic gadolinium oxide micron powder with a particle size between 800 nm and 2 μm.
2. The method for preparing cubic gadolinium oxide transparent ceramic for scintillator matrix according to claim 1, characterized in that: In the step S3, during the cold isostatic pressing treatment, the pressure range is 200-300 MPa, and the holding time is 3-6 min; In the step S3, the temperature-raising sintering is low-temperature and normal-pressure long-term sintering, the sintering temperature is 1000-1200° C., and the heat preservation time is 100-300 hours.
Citation Information
Patent Citations
Method for preparing lutetium gadolinium oxide transparent ceramic scintillator
CN101456735A
Microwave burning preparation method of nano gadolinium oxide powder
CN104973615A
Gadolinium oxide-magnesium oxide nano composite ceramic and preparation method thereof
CN109650890A
Preparation method of high-transparency Gd2O3 transparent ceramic material
CN116283289A
High-toughness ceramic sintered compact excellent in thermal stability and its production
JP1994263533A